Penerapan Layanan Konseling Kelompok dalam Mengatasi Kesulitan Belajar Siswa Akuntansi Kelas XI di SMK Negeri 1 Kutacane - Khanza Azahaara Pertiwi; Purbatua Manurung; Afrahul Fadhila Daulai (Tut Wuri Handayani : Jurnal Keguruan dan Ilmu Pendidikan, 2023)
In the current era where the era is competitive, all countries are trying to improve the quality of their education, because the quality of education can improve the welfare of society in a country. The purpose of this study was to find out the applcation of group counseling services for students' learning difficulties at SMK Negeri 1 Kutacane. This research uses Qualitative Research Methods through observation and interviews. Based on the research conducted, it can be concluded that there are still many who underestimate the understanding of difficulties in learning, and the implementation of group counseling has not reached perfection. , because some students take it seriously and some of them follow it as a formality and consider it useless. In addition, the implementation of group counseling is also carried out by supervising teachers by only providing services to students with problems and achievements.